2017
DOI: 10.1080/1331677x.2017.1314822
|View full text |Cite
|
Sign up to set email alerts
|

Predicting tourism demand by A.R.I.M.A. models

Abstract: The paper provides a short-run estimation of international tourism demand focusing on the case of F.Y.R. Macedonia. For this purpose, the Box-Jenkins methodology is applied and several alternative specifications are tested in the modelling of original time series and international tourist arrivals recorded in the period 1956-2013. Upon the outcomes of standard indicators for accuracy testing, the research identifies the model of A.R.I.M.A.(1,1,1) as most suitable for forecasting. According to the research find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 34 publications
(25 reference statements)
0
40
0
1
Order By: Relevance
“…In the ARIMA and SARIMA models, the behavior of a time series is explained from the past observations of the series itself and from the past forecasting errors. Several studies have shown how ARIMA models and their different variants obtain good results in forecasting tourism demand and, in most cases, surpass other time series methods, such as the periodic auto-regression model [32,33], moving averages [34], smoothed exponential [35], non-causal basic structural model [36], and multivariate adaptive regression splines [37], based on these authors who support the use of ARIMA models for predicting tourism demand, has served as an argument in this study to use the models in predicting ham tourism demand. These ARIMA models have the limitation of only detecting linear relationships and assume a probabilistic distribution of the data [38]; they do comply with the validation tests such as the Dickey-Fuller test for unit roots and with the absence of conditioned heteroscedasticity through ARCH (auto-regressive conditional heteroscedastic) models.…”
Section: Methodsologymentioning
confidence: 99%
“…In the ARIMA and SARIMA models, the behavior of a time series is explained from the past observations of the series itself and from the past forecasting errors. Several studies have shown how ARIMA models and their different variants obtain good results in forecasting tourism demand and, in most cases, surpass other time series methods, such as the periodic auto-regression model [32,33], moving averages [34], smoothed exponential [35], non-causal basic structural model [36], and multivariate adaptive regression splines [37], based on these authors who support the use of ARIMA models for predicting tourism demand, has served as an argument in this study to use the models in predicting ham tourism demand. These ARIMA models have the limitation of only detecting linear relationships and assume a probabilistic distribution of the data [38]; they do comply with the validation tests such as the Dickey-Fuller test for unit roots and with the absence of conditioned heteroscedasticity through ARCH (auto-regressive conditional heteroscedastic) models.…”
Section: Methodsologymentioning
confidence: 99%
“…The ARIMA method can be used to predict data that has nonseasonal and seasonal patterns. The ARIMA model for the seasonal data pattern is formulated as in [14] (6) ARIMA models can be used for short-run estimation based on annual, quarterly, monthly or even weekly, daily or hourly data as in [15]. If a good ARIMA model is obtained more than one model, then the best model can be determined using in-sample criteria and out-sample criteria.…”
Section: Arima Methodsmentioning
confidence: 99%
“…Four accuracy measurements were conducted to select the best model from Box-Jenkins approach. Otherwise, the second research by [17] used Macedonia tourism demand from 1956 until 2013 for forecasting. The researcher applied RMSE, MAE, APE, MAPE and TIC to choose forecasting model.…”
Section: Box-jenkins Approachmentioning
confidence: 99%
“…The researcher applied RMSE, MAE, APE, MAPE and TIC to choose forecasting model. For result comparison, model selected in [16] was SARIMA (0,1,1)(0,1,1)12 while model selected in [17] was ARIMA (1,1,1). Another two researches that applied Box-Jenkins approach in fisheries field can be found in [18] and [19].…”
Section: Box-jenkins Approachmentioning
confidence: 99%